2002
DOI: 10.1002/mrd.10173
|View full text |Cite
|
Sign up to set email alerts
|

Comparison between PMSG‐ and FSH‐induced superovulation for the generation of transgenic rats

Abstract: Superovulation protocols using single injections of pregnant mare's serum gonadotropin (PMSG) or minipumps with follicle-stimulating hormone (FSH) were compared in immature Sprague-Dawley (SD) rats. We used the following criteria: total number of ova, rate of fertilization, in vitro embryo development, sensitivity of zygotes to the microinjection of foreign DNA into the pronucleus, and their in-vivo development after transplantation into the oviduct of a recipient. Female SD rats were stimulated with 15 IU PMS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

6
37
1

Year Published

2004
2004
2019
2019

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 47 publications
(44 citation statements)
references
References 47 publications
6
37
1
Order By: Relevance
“…In rats, on the other hand, the effects of treatment for superovulation show major strain differences [3,12]. This could be one of the reasons for the delay in practical treatment (PMSG administration), or in which gonadotrophins are gradually stimulated by constant infusion of purified FSH with a short half-life via a subcutaneously or intraperitoneally implanted osmotic mini-pump [1,5,11]. However, the superovulatory effect is influenced by rat strain in the above-mentioned cases.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In rats, on the other hand, the effects of treatment for superovulation show major strain differences [3,12]. This could be one of the reasons for the delay in practical treatment (PMSG administration), or in which gonadotrophins are gradually stimulated by constant infusion of purified FSH with a short half-life via a subcutaneously or intraperitoneally implanted osmotic mini-pump [1,5,11]. However, the superovulatory effect is influenced by rat strain in the above-mentioned cases.…”
Section: Introductionmentioning
confidence: 99%
“…However, the superovulatory effect is influenced by rat strain in the above-mentioned cases. The other protocol involves the use of immature rats at 4 to 6 weeks of age [1,4,8,11,13,14], which are not regulated by endogenous hormones since rats begin to exhibit stable estrous cycles with a defined 4-day period at around 8 weeks of age. However, the number of collected fertilized eggs is low because immature female rats generally won't mate with adult males [2].…”
Section: Introductionmentioning
confidence: 99%
“…In experimental rats group 100 IU/kg PMSG and 48 h later 100 IU/kg HCG intraperitoneally were injected then 100 IU PBS were injected to the control group. 14 …”
Section: Ovulation Stimulation In Ovariesmentioning
confidence: 99%
“…They found that FSH increases the number of antral and periantral follicles, while LH increases the primary and secondary follicles. 13 Another study by Popova et al 14 14 The objective of this method is to stimulate folliculogenesis and increase the number of oocytes in a cycle. Following hormonal stimulation of ovulation, the levels of ovarian hormones, especially estradiol and progesterone, extend beyond physiological limits.…”
mentioning
confidence: 99%
“…Specifically, eCG or FSH can induce superovulation in rats (Popova et al, 2002), pigs (Manjarin et al, 2009), sheep (Cognie, 1999), and cattle (Small et al, 2009). FSH and LH are both secreted from pituitary gland, and FSH has a short metabolic half-life (Fry et al, 1987).…”
Section: Introductionmentioning
confidence: 99%